The Need to Improve Patient-Centered Outcome Reporting Following Lower Extremity Flap Reconstruction: A Systematic Review and Meta-analysis - Kim, Kevin G.; Tirrell, Abigail R.; Dekker, Paige K.; Haffner, Zoe; Attinger, Christopher E.; Fan, Kenneth L.; Evans, Karen K. (Journal of Reconstructive Microsurgery, 2021)
Introduction Research in lower extremity (LE) wound management involving flap reconstruction has primarily focused on surgeon-driven metrics. There has been a paucity in research that evaluates patient-centered outcomes (PCO). This systematic review and meta-analysis examines articles published between 2012 and 2020 to assess whether reporting of functional and quality of life (QOL) outcomes have increased in frequency and cohesiveness, compared with the previous two decades.Methods PubMed and Ovid were queried with appropriate Medical Subject Heading (MeSH) terms for studies published between June 2012 and July 2020. For inclusion, each study had to report any outcome of any tissue transfer procedure to the LE in comorbid patients, including complication rates, ambulation rates, flap success rates, and/or QOL measures. The PCO reporting prevalence was compared with a previous systematic review by Economides et al which analyzed papers published between 1990 and June 2012, using a Pearson's Chi-squared test.Results The literature search yielded 40 articles for inclusion. The proportion of studies reporting PCO was greater for literature published between 1990 and 2012 compared with literature published between 2012 and 2020 (86.0 vs. 50.0%, p < 0.001). Functional outcomes were more commonly reported between 1990 and 2012 (78.0 vs. 47.5%, p = 0.003); similarly, ambulatory status was reported more often in the previous review (70.0 vs. 40.0%, p = 0.004). This study solely examined the rate at which PCO were reported in the literature; the individual importance and effect on medical outcomes of each PCO was not evaluated.Conclusion Less than 50% of the literature report functional outcomes in comorbid patients undergoing LE flap reconstruction. Surprisingly, PCO reporting has seen a downward trend in the past 8 years relative to the preceding two decades. Standardized inclusion of PCO in research regarding this patient population should be established, especially as health care and governmental priorities shift toward patient-centered care.
Keywords: patient outcome assessment; patient-centered outcomes research; functional outcomes research; surgical flaps; free tissue flaps; lower extremity